FORMATION OF THE PROFESSIONAL COMPETENCE OF FUTURE PRIMARY TEACHERS WITH THE USE OF MODERN TEACHING METHODS - Opanasenko, Nataliia; Chernenko, Halyna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The article considers the problem of formation of professional competence of future primary teachers. The regulatory framework governing the professional activities of teachers in Ukraine (“Concept of development of Pedagogical Education”, “Professional Standard “Primary School Teacher of Secondary Education”) is analyzed. The urgency of the problem of future schoolteachers' professional training for the modern school, which is being studied within the framework of the project “New Ukrainian School – New Teacher” is proved. The definitions of “competence”, “professional competence”, “professionalism” of both national and international scientists are analyzed.It is proved that professional competence is an integrative characteristic of business and personal qualities of a specialist, reflects the level of knowledge, skills and experience required to achieve the goal of a certain type of professional activity, as well as the moral position of a specialist.The article presents modern methods of training future primary school teachers: “design-thinking” as a creative way of thinking, aimed at creating non-standard solutions and innovations for the formation of professional competence of future teachers of primary education (stages of “design- thinking”: empathy, focusing, ideas generation, prototyping, testing); interactive teaching methods (“lotus blossoming”, mixed media, jury, presentations, etc.), focus group research.The article proves the idea that the formation of key competences of students in the New Ukrainian School, competitiveness and ability to enter the world global space depend on the professional competence of the teacher.